Implementasi QRIS dalam KOIN NU LAZISNU Jawa Timur - RAHAYUNINGSIH, EKA; Styawati, Endang; Hasanah, Evi Riadhotun (Jurnal Ilmiah Ekonomi Islam, 2024)
Kotak Infaq Nahdhatul Ulama’ (KOIN NU) is an infaq fundraising activity conducted by Lembaga Amil Zakat, Infaq, and an Shadaqah NU (Lazisnu). With digitalization, this movement is also present in the community by applying QRIS, where people can donate infaq through digital transactions from various platforms with just one QR Code. This study intends to examine how the implementation of QRIS in KOIN NU in Lazisnu Jawa Timur and how the management of KOIN NU funds. These problems are discussed with field research through qualitative descriptive. The primary sources in this study is interview with supervisor of Lazisnu Jawa Timur, while the secondary sources are books, journal, and other reliable sources on official site. The results of this study indicate that the implementation of QRIS in KOIN NU Lazisnu Jawa Timur is suitable for application in cities that are more familiar with digital, especially for the upper middle class. The collaboration of KOIN NU Lazisnu Jawa Timur with OVO in implementing QRIS is one form of innovation and sensitivity of Lazisnu Jawa Timur to be present as a credible philanthropy institution at all times for the community